2012
DOI: 10.1177/1470320312467557
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression patterns for angiotensin receptors in mouse skin and brain

Abstract: Two G-protein-coupled receptors, angiotensin type 1 receptor (AT1R) and type 2 receptor (AT2R), mediate the majority of angiotensin II (Ang II) effects. It has long been believed that the AT2R is reduced to extremely low levels in adulthood but is abundantly expressed in the fetus. However, recent data from rats and mice do not support this notion. Employing Western blot analysis, we found a gradual increase in AT2R protein expression from fetal life to adulthood in brain, heart, lung, liver, and kidney. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…1D1) 1D2) of developing rats from 1 day to 6 wk of age. This expression pattern is similar to that reported previously in the mouse brain stem (15,42). Interestingly, in the pancreas (Fig.…”
Section: Tissue Distribution and Ontogeny Of At 2 R Proteinsupporting
confidence: 76%
See 3 more Smart Citations
“…1D1) 1D2) of developing rats from 1 day to 6 wk of age. This expression pattern is similar to that reported previously in the mouse brain stem (15,42). Interestingly, in the pancreas (Fig.…”
Section: Tissue Distribution and Ontogeny Of At 2 R Proteinsupporting
confidence: 76%
“…documented that this dogma may not be true (42). We found that adult rat (43) and mouse (15) expressed significantly higher AT 2 R protein compared with the fetus and neonate.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The AT 2 R is expressed in the brain and viscera of adult mice and on small‐ to medium‐sized DRG neurons in the adult rat and humans . In human tissue sections, the AT 2 R is expressed on nerve fibers in peripheral nerves, skin, urinary bladder, and bowel .…”
Section: Introductionmentioning
confidence: 99%